Determinants of Indonesian Trade Balance: A Vecm Analysis Approach - Ferdian Adi Cristanto; Prasetyo Ari Bowo (Economics Development Analysis Journal, 2021)
The Trade Balance is one of the indicators used to see the condition of a country's economy, especially in the trade sector. The trade balance value will affect how the state of the national macroeconomic indicators. In addition, the trade balance is used as additional information in determining foreign trade policy. This study aims to analyze the factors that affect Indonesia's trade balance in 2010-2019. The variables used are investment, rupiah exchange rate, economic growth and trade balance. The method used in this research is VECM (Vector error correction model) analysis with time series data using Eviews 9.0 data processing software. The results show that (1) direct investment has a significant positive effect in the short and long term, (2) exchange rate has a significant negative effect in the long term. short and long term, and (3) economic growth has no significant effect in the short and long term on Indonesia's trade balance